2005
DOI: 10.1038/sj.npp.1300933
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Prevents 5-HT1A Receptor-Induced Disruptions of Prepulse Inhibition in Healthy Women

Abstract: The sex steroid hormone, estrogen, has been proposed to be protective against schizophrenia. This study examined the effects of estrogen treatment on modulation of prepulse inhibition (PPI) by the serotonin-1A (5-HT 1A ) receptor partial agonist, buspirone. PPI is a model of sensorimotor gating, which is deficient in schizophrenia and other mental illnesses. A total of 11 healthy women were tested following four acute treatment conditions: placebo, buspirone (Buspar; 5 mg), estradiol (Estrofem; 2 mg), and comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 36 publications
8
39
0
Order By: Relevance
“…Following ATD we observed impairments in sensorimotor gating, as evidenced by a reduction in PPI. This finding directly supports a number of studies that have similarly found a decrease in PPI following a reduction in serotonergic neurotransmission in healthy humans, with ATD (Phillips et al, 2000a), the 5-HT 2 receptor antagonist ketanserin (Graham et al, 2002), and the 5-HT 1A partial agonist buspirone (Gogos et al, 2006). The findings also concur with a number of studies that report the opposite effect (ie an increase in PPI with enhancement of serotonergic neurotransmission) with MDMA (Liechti et al, 2001) and the 5-HT 2A/1A agonist psilocybin (Gouzoulis-Mayfrank et al, 1998;Vollenweider et al, 1999).…”
Section: Serotonin Depletionsupporting
confidence: 87%
See 4 more Smart Citations
“…Following ATD we observed impairments in sensorimotor gating, as evidenced by a reduction in PPI. This finding directly supports a number of studies that have similarly found a decrease in PPI following a reduction in serotonergic neurotransmission in healthy humans, with ATD (Phillips et al, 2000a), the 5-HT 2 receptor antagonist ketanserin (Graham et al, 2002), and the 5-HT 1A partial agonist buspirone (Gogos et al, 2006). The findings also concur with a number of studies that report the opposite effect (ie an increase in PPI with enhancement of serotonergic neurotransmission) with MDMA (Liechti et al, 2001) and the 5-HT 2A/1A agonist psilocybin (Gouzoulis-Mayfrank et al, 1998;Vollenweider et al, 1999).…”
Section: Serotonin Depletionsupporting
confidence: 87%
“…It could be argued that the positive effects of MDMA and psilocybin may be mediated by their effects on other neurotransmitter systems, including dopamine or noradrenaline, rather than their serotonergic actions. However, this is unlikely as we and others have shown a decrease in PPI following ATD (in this study and Phillips et al, 2000a) and with the 5-HT 1A agonist, buspirone (Gogos et al, 2006). It is more likely that effects are related to the potency of serotonergic modulation.…”
Section: Serotonin Depletionmentioning
confidence: 64%
See 3 more Smart Citations